Act of Phytochemical-Based Antioxidants in Neurodegenerative Disorders Utilizing Indian Medicinal Plants - Navya Raj MP; Pooja G Singh; Sushma BV (International Journal of Pharma and Bio Sciences, 2021)
Neurodegenerative diseases are multifactorial nervous system deteriorating conditions that concern over 30 million aging populations worldwide. The effect of protein malfunction or defective trafficking is neurodegenerative disease, such as Alzheimer disease [AD], Parkinson’s disease [PD], Huntington's and Amyotrophic lateral sclerosis disorders. Furthermore, mitochondrial dysfunction, oxidative stress / age-linked environmental factors have also been involved. Prolonged use of synthetic medications could lead to adverse side effects for these illnesses. Henceforth herbal therapy attracts much attention rather than a pharmaceutical therapy is favoured. Indeed, several research studies have identified use of medicinal plants and their components for drug production, and recently more than 100 new medicines are now being established clinically. Accumulative data shows that nutraceuticals property is critical for cognition optimisation and risk mitigation. The study explores the role of phytochemical based antioxidants in cognitive and adverse signal transduction events, with a special focus on the Mediterranean diet [MeDi] comprising bioactive compounds like - xanthophyll carotenoids and omega-3 fatty acids. These phytochemical compounds are capable of improving cognition, considering their selective brain involvement and their specifically oxidative damage and inflammation. The objective of this study is to detail the molecular mechanisms of some Ayurvedic plants signal transduction and locations of operation. It is hoped that this review further helps to examine a new therapeutic recommendations and further research in clinical trials on the use of poly-herbal Ayurvedic medicine for the treatment and prevention of dementia. It is expected to increase the ease in the usage of Ayurveda-based knowledge base combined with combined scientific and high-performance screening strategies in the drug research and development campaign, while offering new practical guidelines for neurosurgical diseases linked to age.